2014
DOI: 10.1186/1471-2407-14-697
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of use of radiotherapy for lung cancer: a descriptive study

Abstract: BackgroundLung cancer remains one of the most prevalent forms of cancer. Radiotherapy, with or without other therapeutic modalities, is an effective treatment. Our objective was to report on the use of radiotherapy for lung cancer, its variability in our region, and to compare our results with the previous study done in 2004 (VARA-I) in our region and with other published data.MethodsWe reviewed the clinical records and radiotherapy treatment sheets of all patients undergoing radiotherapy for lung cancer durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…It is reported that CD68 + HLA-DR + TAMs in hepatocellular carcinoma (HCC) can promote migration of HCC cells via the NF- κ B/FAK pathway [66]. Specifically, TAM-derived IL-6 and IL-8 enhance invasive activity of LoVo cells induced by PRL-3 in a KCNN4 channel-dependent manner [67]. …”
Section: Tams Remodel the Tumor Microenvironmentmentioning
confidence: 99%
“…It is reported that CD68 + HLA-DR + TAMs in hepatocellular carcinoma (HCC) can promote migration of HCC cells via the NF- κ B/FAK pathway [66]. Specifically, TAM-derived IL-6 and IL-8 enhance invasive activity of LoVo cells induced by PRL-3 in a KCNN4 channel-dependent manner [67]. …”
Section: Tams Remodel the Tumor Microenvironmentmentioning
confidence: 99%
“… 3 Commonly accepted, radiotherapy, chemotherapy, traditional Chinese medicine, and their conjunctions are the approaches for lung cancer treatment. 4 7 Despite significant advances made in research into the progression, development, and prognosis of lung cancer over the past few decades, the outcome of most patients afflicted with lung cancer has not remarkably improved. Recently, researchers have disclosed that the vast majorities of human genome are indeed transcribed into various types of non-coding RNAs (ncRNAs) without protein-coding ability, including small ncRNAs (RNA transcript length <200 nt) and long ncRNAs (lncRNAs, RNA transcript length >200 nt).…”
Section: Introductionmentioning
confidence: 99%
“…Style of practice: medical practice patterns may explain the low irradiation rates found in our region [36,37]. Most clinical trials have a control arm with standard treatment that does not include RT [38,39].…”
Section: Discussionmentioning
confidence: 99%